2005
DOI: 10.5432/ijshs.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging of Human Skeletal Muscle During Movement: Implications for Recruitment, Metabolism and Circulation

Abstract: Imaging is a powerful strategy for the visualization of anatomical and functional information (levels and patterns of activation, perfusion, circulation, and metabolism etc.) in human skeletal muscle. Recent innovations in scientific technology, several new techniques and methods have been developing that visualize the function of muscle regarding recruitment, perfusion, and/or metabolism in exercise. This review is focused on three novel imaging techniques; magnetic resonance imaging, positron emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 95 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…The findings suggest that signal intensity changes are associated with task-dependent differences and likely influenced by metabolic demand and/or neural activation. 3 mfMRI also offers clinical insight into the effectiveness of an exercise to target a specific muscle or muscle group. Takeda et al 56 demonstrated significantly greater increases in T2 relaxation time for the supraspinatus muscle in response to empty-can and full-can exercises (shoulder abduction performed in the scapular plane with thumb down and up, respectively) in comparison to a horizontal abduction exercise in healthy individuals.…”
Section: Muscle Function During Specific Exercise/rehabilitation Protmentioning
confidence: 99%
“…The findings suggest that signal intensity changes are associated with task-dependent differences and likely influenced by metabolic demand and/or neural activation. 3 mfMRI also offers clinical insight into the effectiveness of an exercise to target a specific muscle or muscle group. Takeda et al 56 demonstrated significantly greater increases in T2 relaxation time for the supraspinatus muscle in response to empty-can and full-can exercises (shoulder abduction performed in the scapular plane with thumb down and up, respectively) in comparison to a horizontal abduction exercise in healthy individuals.…”
Section: Muscle Function During Specific Exercise/rehabilitation Protmentioning
confidence: 99%
“…The transverse relaxation time (T 2 ) of exercised muscle is greater than that of muscle at rest, [1][2][3] and Akima and associates proposed muscle functional magnetic resonance imaging (mfMRI) 4,5 to visualize the enhanced activity. However, its use with spin echo (SE) sequence to calculate T2 requires minutes of the acquisition time and is limited to the limbs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] For example, Adams and associates used shifts in contrast on MR images in an attempt to map regions of the thigh muscle stimulated by transcutaneous electromyostimulation (EMS). 11 Similarly, Akima's team tested the coactivation patterns of individual muscles and the neuromuscular compartments of the quadriceps femoris during knee-extension exercises.…”
Section: Introductionmentioning
confidence: 99%
“…14 In particular, they proposed muscle functional MR imaging (mfMRI) as a technique for visualizing muscle activity from T 2 changes. 14,16 However, mfMRI uses a spin-echo (SE) or multiple spin-echo (MSE) sequence to calculate T 2 , both of which require several minutes for acquisition. Unfortunately, the duration of conventional imaging techniques is restricted, so mfMRI can only be applied to the limbs.…”
Section: Introductionmentioning
confidence: 99%